Performance evaluation of dynamic voltage restorer using bidirectional impedance converter with UCAP - A. Anitha; K. C. R. Nisha (Institute of Advanced Engineering and Science, 2026)
With the involvement of renewable energy sources, plug-in hybrid automobiles, and fault occurrence, power quality has degraded nowadays. The most effective device utilized in distribution systems to enhance power quality is the dynamic voltage restorer (DVR). For deep sags, DVR with storage topology is more beneficial, although it has challenges with converter and storage element rating. To address this, various converters and energy storage elements like ultracapacitors are reviewed. In this paper, a DVR with an ultra-capacitor (UCAP) using an impedance bidirectional converter is simulated, and power quality indices are compared with VSI-BDC. The simulation result reflects the enhanced capability of the suggested DVR in a wide range of operations, improved power quality indices, and its effectiveness in swell conditions. The control of DC link voltage with PI and model predictive control (MPC) were simulated and compared.